A substrate binding model for the KEOPS tRNA modifying complex - Jonah Beenstock; Samara Mishelle Ona; Jennifer Porat; Stephen Orlicky; Leo C. K. Wan; Derek F. Ceccarelli; Pierre Maisonneuve; Rachel K. Szilard; Zhe Yin; Dheva Setiaputra; Daniel Y. L. Mao; Morgan Khan; et al. (Nature Communications)
Abstract The KEOPS complex, which is conserved across archaea and eukaryotes, is composed of four core subunits; Pcc1, Kae1, Bud32 and Cgi121. KEOPS is crucial for the fitness of all organisms examined. In humans, pathogenic mutations in KEOPS genes lead to Galloway–Mowat syndrome, an autosomal-recessive disease causing childhood lethality. Kae1 catalyzes the universal and essential tRNA modification N6-threonylcarbamoyl adenosine, but the precise roles of all other KEOPS subunits remain an enigma. Here we show using structure-guided studies that Cgi121 recruits tRNA to KEOPS by binding to its 3’ CCA tail. A composite model of KEOPS bound to tRNA reveals that all KEOPS subunits form an extended tRNA-binding surface that we have validated in vitro and in vivo to mediate the interaction with the tRNA substrate and its modification. These findings provide a framework for understanding the inner workings of KEOPS and delineate why all KEOPS subunits are essential.